AN EXAMPLE OF DOUBLE FOURIER–HAAR SERIES WITH A NONREGULAR SUBSERIES - Keryan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
We bring an example of integrable function on $[0;1]^2$, so that the double Fourier–Haar series has a subseries, whose majorant of partial sums does not belong to $ L^{1, ∞}$.
Keywords: double Haar series, majorant, square function, $A$-integral